RESEPSI ESTETIS QUR’ANI DALAM MUSIK ROCK SHOLAWAT ROFA BAND DI BANTUL YOGYAKARTA - Khosim, Mochamad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2019)
A Muslim’s interaction with the Quran directly both verbally, in writing, and with the form of practice results in different experiences arising in each individual. The process which then gave birth to traditions and various kinds of receptions on understanding the meaning of the verses of the Quran. From this phenomenon the author tries to examine the aesthetic reception of a Kyai in Islamic boarding school Rouḍotul Fatiḥâh on the art of music in a music community called the Rofa Band. To find out the background of the creation of the Rofa Band and the meaning of the songs delivered. Also tried to reveal from the aspect of how scientific transmission and transformation carried out by KH. Fuad Riyadi related it to the reception of the Quran verses in the practice of Rofa Band. As a theoretical basis, researchers use a theory conceived by Peter L. Berger and Thomas Luckmann which states that social construction is inseparable from the historical process that connects traditional spaces. The results of the research by the author show that the reason for the formation of Rofa Band by Gus Fuad was motivated by Gus Fuad’s anxiety about the rise of the influence of Western music for the community, secondly, encouragement from one of his teachers, and third, Gus Fuad’s desire to convey the message of the Prophet’s love through the art of music. The meaning of the Rofa Band songs that Gus Fuad wants to convey the magnitude of the love and love of the Apostle to his people. Keyword: Reception, Tradition, Living Quran, Transmission, Transformation
Keywords: Resepsi; Tradisi; Living Qur’an; Transmisi; Transformsi